Mast Cell: An Emerging Partner in Immune Interaction - Gri, Giorgia; Frossi, Barbara; D'Incà, Federica; Danelli, Luca; Betto, Elena; Mion, Francesca; Sibilano, Riccardo; Pucillo, Carlo (Frontiers in Immunology, 2012)
Mast cells (MCs) are currently recognized as effector cells in many settings of the immune response, including host defense, immune regulation, allergy, chronic inflammation and autoimmune diseases. MC pleiotropic functions reflect their ability to secrete a wide spectrum of preformed or newly synthesized biologically active products with pro-inflammatory, anti-inflammatory and/or immunosuppressive properties, in response to multiple signals. Moreover, the modulation of MC effector phenotypes relies on the interaction of a wide variety of membrane molecules involved in cell-cell or cell-extracellular-matrix interaction. The delivery of co-stimulatory signals allow MC to specifically communicate with immune cells belonging to both innate and acquired immunity, as well as with non-immune tissue-specific cell types. This article reviews and discuss the evidence that MC membrane-expressed molecules play a central role in regulating MC priming and activation and in modulation of innate and adaptive immune response not only against host injury, but also in peripheral tolerance and tumor-surveillance or -escape. The complex expression of MC surface molecules may be regarded as a measure of connectivity, with altered patterns of cell-cell interaction representing functionally distinct MC state. We will focalize our attention on role and functions of recently discovered molecules involved in the cross-talk of MCs with other immune partners.